Investigation of life style and personal habits of wrestling referees - Çınar, Vedat; Öner, Salih; Akbulut, Taner; Pala, Ragıp (My University, 2016)
OBJECTIVE: The aim of this study was to investigate of life style and personally habits of referees who working in the Turkey Wrestling Federation. METHODS: The population of the research was Turkey Wrestling Federation referees, the samples of research created from 108 male coach who participated Turkey Championship stars catagories in 2015 april. In this study was used "Healthy Lifestyle Behaviors Scale’’. The data obtained from the questionnaire results were analyzed with SPSS 17 software package. One Way Anova and Independent Samples t tests were used to analyze the data to determine the differences between the groups. RESULTS: The data obtained from the survey results mean values of referees were found 131.21±15.01 point (min:98, max:169). To contribute behaviors for development of health the highest mean scores, self-actualization, health responsibility, which found support in stress management and interpersonal dimension respectively, and the lowest average exercise and eating habits. There were no significant relation on healty life style behaviors of age, category, occupation time and smoking. Referees who new starting to work has higher nutrition level than old referees. CONCLUSIONS: As a result, coach who working in Turkey Wrestling Federation have low life style and personal habits. Therefore it could say that to gain these behaviors can be helpful. Keywords: Lifestyle,
Bildiri - Yayımlanmamış
Keywords: Lifestyle; Wrestling; Referee; Habit